IMPLEMENTASI MODEL GUIDED INQUIRY BERBANTUAN SOCRATIC QUESTIONING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MURID SMP PADA MATERI PENCEMARAN - Cahya Haqiqi, Maharani; Ayu Permata Sari, Dhita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of science learning, the improvement of students’ critical thinking skills, and students’ responses after the application of the guided Inquiry learning model assisted by socratic questioning on pollution topics. The study employed a quantitative approach with a preexperimental design using a one-group pretest-posttest design. The research was conducted at SMP Negeri 22 Surabaya with 33 seventh-grade students from class VII-F as participants. The measurement of critical thinking skills was based on five indicators proposed by Ennis (2011), namely providing simple explanations, building basic skills, making inferences, providing further explanations, and setting strategies and tactics. Data were collected through observation, tests, and questionnaires. Data analysis included N-Gain to determine the improvement of critical thinking skills, a normality test to examine data distribution, and the Wilcoxon test to analyze differences between pretest and posttest results. The analysis of learning implementation and student responses used Likert-scale questionnaires analyzed based on the mode value. The results showed that the implementation of learning across three meetings was categorized as very good. Furthermore, students’ critical thinking skills improved, as indicated by the N-Gain scores in each aspect: providing simple explanations (0.63, moderate), building basic skills (0.56, moderate), making inferences (0.84, high), providing further explanations (0.70, high), and setting strategies and tactics (0.76, high). Students’ responses to the learning process were also categorized as very good. Therefore, the application of the guided Inquiry learning model assisted by socratic questioning contributes positively to improving students’ critical thinking skills on pollution topics.